2021
DOI: 10.3390/covid1030049
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Movement Control Order for Various Population Mobility Phases during COVID-19 in Malaysia

Abstract: Background: COVID-19 was declared a pandemic by the World Health Organization on 11 March 2020. From the beginning of the pandemic, there was no effective pharmaceutical intervention to halt or hold up the spread of this novel disease. Therefore, most countries, including Malaysia, resorted to break the chain of transmission by restricting population mobility through the implementation of the Movement Control Order (MCO). We aim to determine the population mobility trend across the various phases of the MCO du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The results of the present study showed a positive effect of the movement control order (MCO) in Malaysia to increase university students' adherence to COVID-19 protective measures (avoidance of crowded places, wearing face masks, and proper hand hygiene). This result was consistent with that found in other studies conducted in Malaysia (16,17) .…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study showed a positive effect of the movement control order (MCO) in Malaysia to increase university students' adherence to COVID-19 protective measures (avoidance of crowded places, wearing face masks, and proper hand hygiene). This result was consistent with that found in other studies conducted in Malaysia (16,17) .…”
Section: Discussionsupporting
confidence: 93%
“…January 2021 indicated the implementation of Movement Control Order 2.0 (MCO 2.0), which involved 6 out of 14 states in the country. Although the MCO 2.0 was not nationally implemented, the average mobility trend of the population was generally reduced at the national level 26 ; hence, it is considered as one of the interruption points in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, Malaysia has undergone a variety of restriction movement policies, such as the Movement Control Order (MCO) and the National Recovery Plan (NRP). The restrictions made by the Malaysian government have caused activity-related travel behaviour to be limited in which; people in essential sectors are allowed to go out to work, while those in non-essential sectors are encouraged to work from home ( Rajendran et al, 2021 , Tay et al, 2021 ), and influenced the people's risk perception of getting an infection while travelling ( Md Yusuf & Azhar, 2021 ). The public's mental health and well-being are impacted when their ability to travel is impeded ( Knolle et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%